(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Technological advances have a major influence on human life, including in the field of education, one of which is in the form of learning media. The development of learning media presents challenges for teachers, especially Early Childhood Education (PAUD) teachers who rely on media to visualize everything students learn as part of their literacy skills. However, the reality is that not all teachers are prepared to create learning media to improve children’s literacy skills. For this reason, assistance for PAUD teachers is needed in making learning media, especially cartoon animation media that can be designed according to the wishes of the teachers. Therefore, Community Service this time chose the title Assistance in Making Cartoon Animation Media for Teachers to Stimulate Students’ Literacy Ability at the Center for Early Childhood Education (PKG-PAUD) Activities, Bojongsoang District, Bandung Regency. The results of the activity showed an increase in the ability to make animated cartoons by 75.09% accompanied by a positive response from the teachers.